Ligands of HMG-like dorsal switch protein 1 of Spodoptera exigua leads to mortality in diamondback moth, Plutella xylostella - Md. Mahi Imam Mollah (Heliyon, 2024)
HMG-like dorsal switch protein 1 (DSP1) is the insect homolog of the high mobility group box 1 (HMGB1) protein of the vertebrates. Previous studies confirmed DSP1 in Spodoptera exigua, Tenebrio molitor, and Aedes albopictus, and were analyzed for their immune roles, survivability, and binding affinity with entomopathogenic bacterial metabolites. The present study aimed to predict, and confirm DSP1 in diamondback moth, Plutella xylostella along with the effect of Spodoptera exigua DSP1 ligands in the survivability of this insect. DSP1 of Plutella xylostella (Px-DSP1) consists of 465 amino acids (AA). Phylogeny analysis showed that Px-DSP1 clustered with other Lepidopteran insects where each insect order clustered separately. Domain analysis showed that like other insects, Px-DSP1 contains two HMG boxes (Box A and Box B), one coiled-coil (CC), five Q-rich low complexity (LC), and an acidic tail (AT). Px-DSP1 was expressed in each developmental stage and tissue. The highest expression was in L4 larvae and fat body tissues. Thermal shift assay (TSA) showed the binding affinity of 3-Ethoxy-4-Methoxyphenol (EMP), Phthalimide (PM), and o-Cyanobenzoic acid (CBA) to rDSP1 of Spodoptera exigua. Mortality bioassay showed that all these metabolites were toxic against P. xylostella larvae. Among these, EMP was more toxic providing more than 65% mortality at 500 ppm concentration. However, PM and CBA also showed more than 60 and 50% mortality, respectively at 500 ppm concentration. We assume that like Se-DSP1, these compounds also bind with Px-DSP1 which leads to the inhibition of DSP1-mediated immunity and impose the mortality of Plutella xylostella larvae.